Nine level switched capacitor inverter with level shifted pulse width modulation approach - Arun, Vijayakumar; Prasad, Thunga Nageswara; Prabhu, Sundaramoorthy; Ashokkumar, Nagarajan (International Journal of Applied Power Engineering (IJAPE), 2024)
This article proposes a nine-level switched capacitor inverter (NLSCI) with a minimum number of switches. In recent years, switching capacitor (SC) multilevel inverters (MLIs) have become one of the most common inverter topologies. These proposed nine level switched capacitor inverter (NLSCI) do not deserve any external control unit for capacitor control. Since, the charging and discharging of the capacitors are controlled by the on and off states of switches. Furthermore, by employing fewer switches and DC voltage sources, the suggested design produces a greater amount of resultant voltage. Additionally, pulse width modulation (PWM) is recommended as a method to enhance output quality and power level quality. The switched-capacitor two-output multilevel inverter (SCMLI) structure's viability and effectiveness have been demonstrated using MATLAB simulation.